Evaluating Clinical Outcomes for Determining the Optimal Delay to Skin Incision under WALANT: A Prospective Series of 34 Patients from a Low-Resource Tertiary Setting - Alvin Hernandez; Mamer Rosario; Romina Mendoza-Torres; Carl Ryan Marino Taguba; Abigail Garcia; Geoffrey Battad (Advances in Orthopedics)
Background. Additional studies on clinical outcomes to determine the optimal time delay from injection of local anesthesia to skin incision for WALANT surgeries are needed. The authors aimed to propose the optimal time delay from local injection to skin incision for WALANT surgeries of the hand and wrist by analyzing intraoperative blood loss, postoperative pain scores, and complication rates. Methods. Thirty-four patients were consecutively recruited and allocated by either 7-min or 30-min delay for skin incision from local injection of epinephrine with lidocaine. Intraoperative bleeding and postoperative pain scores were analyzed between both groups by Mann–Whitney U-test, while complication rates were compared using Fisher’s exact test. Results. The present study did not find significant differences in mean intraoperative blood loss (8 ± 5.8 mL vs. 5 ± 2.2 mL, p=0.074), complication rates (18% vs. 0%, p=0.227), and mean pain scores (1.2 ± 0.5 vs. 1.4 ± 0.5, p=0.307) between the 7-min and 30-min groups. Conclusion. The authors conclude that a waiting time of 7 min from the injection of local anesthesia is sufficient to achieve comparable clinical outcomes for minor hand and wrist surgeries under WALANT.